Ocurrence of the sea anemone Telmatactis panamensis (Verrill, 1869) (Cnidaria: Anthozoa: Actiniaria) at Isla del Coco National Park, Costa Rica - Acuña, Fabián H.; Cortés, Jorge; Garese, Agustín (Revista de Biología Tropical, 2012)
The sea anemone fauna of Isla del Coco National Park (also known as Cocos Island Nacional Park), Pacific Costa Rica is poorly known. In the present work we report the first occurrence of the species Telmatactis panamensis. Individuals of this sea anemone (n=24) were collected at Chatham Bay intertidal and at 15m depth in Punta Ulloa, in both cases attached to rocks; during the expedition UCR-UNA-COCO-I in April 2010. We provide photographs of live individuals, external anatomy and an inventory of cnidae of the studied specimens. Possibly this species is extended to greater depth as observed by other authors in the Galápagos Islands. Citation: Acuña, F.H., J. Cortés & A. Garese. 2012. Ocurrence of the sea anemone Telmatactis panamensis (verrill, 1869) (Cnidaria: Anthozoa: Actiniaria) at Isla del Coco National Park, Costa Rica. Rev. Biol. Trop. 60 (Suppl. 3): 201-205. Epub 2012 Dec 01.